Unlocking Architecture and Heritage Potential for Village Tourism in Lahat Regency - Prima, Listen; Lussetyowati, Tutur; Adiyanto, Johannes (Humaniora: Journal of Indonesia Culture and Society, 2026)
Cultural heritage plays a vital role in supporting sustainable development, particularly within the growing field of heritage-based tourism. Tinggi Hari Village in Lahat Regency, South Sumatra Province, offers a distinctive combination of cultural and natural attractions, which positions it as a valuable site for integrated tourism development. The village’s key heritage assets include the megalithic sites, which are considered among the oldest in Southeast Asia, and the traditional Rumah Baghi architecture, which embodies vernacular knowledge, social values, craftsmanship, and historical continuity. Despite the richness of these resources, existing development programs tend to manage them in isolation or to overlook their interconnected significance, resulting in underutilised potential, fragmented planning, and limited benefits for local communities. This research addresses the lack of a comprehensive framework that connects cultural heritage with the surrounding natural environment. Adopting a case study methodology, this study combines field surveys, in-depth interviews with experts and community leaders, and spatial mapping analysis to explore viable pathways for integrating megalithic heritage, Rumah Baghi architecture, and natural landscapes into a cohesive cultural heritage tourism strategy. The findings reveal that aligning tangible heritage assets with environmental features not only enriches the visitor experience but also reinforces local identity, enhances conservation awareness, and contributes to economic resilience. The proposed integrative model provides practical insights and strategic guidance for heritage-rich rural areas that seek to advance sustainable development through culturally grounded and community-centred tourism initiatives.